Synergistic Impact of Cholesterol-Loaded Cyclodextrin and Moringa Leaf Extract on Post-Thaw Boar Sperm Kinematics - Hine, T. M.; Nalley, W. M.; Uly , K.; Kune , P.; Lawa , A. B.; Setyani , N. M. P.; Bette , Y. Y.; Banamtuan , A. N.; Riwu , R. M. J. (Faculty of Animal Science, IPB University, 2026)
Structural and functional damage during cryopreservation usually impairs the quality of boar sperm, especially post-thaw motility and kinematic performance, which restricts its use in artificial insemination programs. Cholesterol-loaded cyclodextrin (CLC) and moringa leaf extract (MLE) are considered possible cryoprotective additives because they are membrane-stabilizing and antioxidants. The study investigated the possible synergistic effect of the Tris-egg yolk (TY) extender in combination with CLC and MLE on the motility and kinematics properties of thawed boar sperm, as identified in a Computer-Assisted Sperm Analysis (CASA) system. Ejaculates of four healthy boars were diluted with Tris-based extender without or with CLC (1 or 2 mg/mL), MLE (1 or 1.5 mg/mL), or both, and frozen with a conventional protocol. Kinematic variables alongside progressive and fast motility were included as post-thaw tests. The findings showed that combination treatment of 2 mg/mL CLC and 1 mg/mL MLE (T7) resulted in a significant increase in all sperm motility and kinematic variables compared to the control group (T0) (p<0.05). In particular, T7 had better progressive motility (38.04%), fast motility (22.42%), and higher kinematic variables, especially VCL (106.34 µm/s), VSL (36.28 µm/s), and VAP (45.41 µm/s), and better displacement and trajectory indices. T7 was always better than the single supplementation and other combinations. Finally, the addition of CLC (2 mg/mL) and MLE (1 mg/mL) into the Tris egg yolk extender could be a successful approach towards optimizing semen cryopreservation in boars.